Prevention of incisional hernia with prophylactic onlay and sublay mesh reinforcement vs. primary suture only in midline laparotomies (PRIMA): long-term outcomes of a multicentre, double-blind, randomised controlled trial - Dop, Matthijs van den; Sneiders, Dimitri; Yurtkap, Yagmur; Werba, Alexander; van Klaveren, David; Pierik, Robert E. G. J. M.; Reim, Daniel; Timmermans, Lucas; Fortelny, René H.; Mihaljevic, André L.; Kleinrensink, Gert-Jan; Tanis, Pieter J.; et al. (The lancet. Regional health, 2024)
Background - Incisional hernia occurs approximately in 40% of high-risk patients after midline laparotomy. Prophylactic mesh placement has shown promising results, but long-term outcomes are needed. The present study aimed to assess the long-term incisional hernia rates of the previously conducted PRIMA trial with radiological follow-up. - Methods - In the PRIMA trial, patients with increased risk of incisional hernia formation (AAA or BMI ≥27 kg/m2) were randomised in a 1:2:2 ratio to primary suture, onlay mesh or sublay mesh closure in three different countries in eleven institutions. Incisional hernia during follow-up was diagnosed by any of: CT, ultrasound and physical examination, or during surgery. Assessors and patients were blinded until 2-year follow-up. Time-to-event analysis according to intention-to-treat principle was performed with the Kaplan-Meier method and Cox proportional hazard models. Trial registration: NCT00761475 (ClinicalTrials.gov). - Findings - Between 2009 and 2012, 480 patients were randomized: 107 primary suture, 188 onlay mesh and 185 sublay mesh. Five-year incisional hernia rates were 53.4% (95% CI: 40.4-64.8), 24.7% (95% CI: 12.7-38.8), 29.8% (95% CI: 17.9-42.6), respectively. Compared to primary suture, onlay mesh (HR: 0.390, 95% CI: 0.248-0.614, p < 0.001) and sublay mesh (HR: 0.485, 95% CI: 0.309-0.761, p = 0.002) were associated with a significantly lower risk of incisional hernia development. - Interpretation - Prophylactic mesh placement remained effective in reducing incisional hernia occurrence after midline laparotomy in high-risk patients during long-term follow-up. Hernia rates in the primary suture group were higher than previously anticipated. - Funding - B. Braun.
Online verfügbar: 22. November 2023, Artikelversion: 2. Januar 2024
Gesehen am 21.06.2024